Try it Together - Qualitative coding with Atlas.ti - DONG, Danping (Institutional Knowledge at Singapore Management University, 2024)
This hands-on session introduces Atlas.ti, a well-established qualitative data analysis tool for analyzing your transcripts and textual data. The session will cover coding data, extracting insights, creating visualizations, and exploring the tool's latest AI features.